Dysbiosis of the Gut Microbiome in Lung Cancer - Zhuang, He; Cheng, Liang; Wang, Yao; Zhang, Yu-Kun; Zhao, Man-Fei; Liang, Gong-Da; Zhang, Meng-Chun; Li, Yong-Guo; Zhao, Jing-Bo; Gao, Yi-Na; Zhou, Yu-Jie; Liu, Shu-Lin (Frontiers in Cellular and Infection Microbiology, 2019)
Lung cancer (LC) is one of the most serious malignant tumors, which has the fastest growing morbidity and mortality worldwide. A role of the lung microbiota in LC pathogenesis has been analyzed, but a comparable role of the gut microbiota has not yet been investigated. In this study, the gut microbiota of 30 LC patients and 30 healthy controls were examined via next-generation sequencing of 16S rRNA and analyzed for diversity and biomarkers. We found that there was no decrease in significant microbial diversity (alpha diversity) in LC patients compared to controls (P observed = 0.1422), while the composition (beta diversity) differed significantly between patients and controls (phylum [stress = 0.153], class [stress = 0.16], order [stress = 0.146], family [stress = 0.153]). Controls had a higher abundance of the bacterial phylum Actinobacteria and genus Bifidobacterium, while patients with LC showed elevated levels of Enterococcus. These bacteria were found as possible biomarkers for LC. A decline of normal function of the gut microbiome in LC patients was also observed. These results provide the basic guidance for a systematic, multilayered assessment of the role of the gut microbiome in LC, which has a promising potential for early prevention and targeted intervention.